Constraints to commercializing potato in Kenya. - Ng'ang'a, N.; Otieno, S.; Mbiu, M.; Lung'aho, C.; Wasilwa, L. (2014)
Although potato is an important source of food and income in Kenya, poor yields and erratic returns have constrained profitability and expansion of the crop. The objective of this study was to describe the potato production system, identify constraints, and determine levels of use of inputs; and the profitability of potato as a business in 4 out of the 10 most important potato producing Counties. We used multistage sampling to select 390 farmers from 4 of the 10 most important potato producing Counties. A questionnaire was used to collect information from farmers and means were separated using ANOVA. Results showed that farming was the main source of income for both husband and wife in at least 66% of households and these where fairly young families with the household heads aged 45 years; having 15years of experience in potato production, and having had 13 years of schooling-with significant differences across regions. Potatoes were grown principally by small-holder farmers twice a year on about 0.92 acres in the March/May season and 0.87acres in the September/October season with significant differences across regions. There was uniformity in variety choice with Changi being predominant in three out of the four Counties. Productivity was at a sub-optimal level with yields of 5.6tons/ha compared to an African average of 10.8tons/ha (CIP 2007) - with significant regional differences. The low productivity can be partially explained by the low input use (seed and fertilizer) which was well below what was recommended by the Government extension officers. The quality of the seed used was of doubtful quality as it was not certified seed but sourced mainly from own harvest, from neighbors or from nearby primary markets. Despite all these shortcomings potato production gave farmers a gross income of about $1240 in the March/May season and $1173 in the Oct/Sept and this was above the UN poverty level of $1.5 per day (or approx. $270 per season of 6 months) -with that income differing significantly across regions. Potato thus has the potential to significantly impact the food and income situations of small-holder farmers in Kenya if the identified constraints can be addressed in socially and economically acceptable ways.